The very marrow of the national idea: The Frontier Wars and the Australian curriculum - Bedford, Alison; Kerby, Martin; Baguley, Margaret; Maddock, Daniel (Historical encounters, 2023)
Prior to the 1970s Indigenous issues were largely absent from Australian history classrooms. Schools largely taught British and European history, an approach grounded in a hagiographic treatment of European settlement and the nation’s experience of foreign wars. The wave of non-British post-Second World War migration and an increased focus on Australia’s relationship with the United States, including its strategic importance as a Pacific nation, made a white, male, mono-cultural national identity increasingly difficult to maintain. Political parties from the Left and Right have repeatedly clashed over their competing conceptions of the core elements of Australia’s national identity, which in turn has underpinned a sustained controversy over the development of a national history curriculum and the classroom practice it shapes. In particular, the question of how the Australian Frontier Wars can be taught within a socio/cultural context that celebrates foreign wars as the birthplace of the nation and considers European settlement to be an overwhelmingly benign process is one of the central controversies that has marred the development and evolution of the Australian Curriculum: History.